The Learning Difficulties of International Students in Universitas Negeri Padang and Universitas Jambi and its Implication of the Role of Guidance and Counseling - Yadanar Thein, Phyu Sin; Ardi, Zadrian (Universitas Negeri Padang, 2023)
Learning difficulties is used to describe a variety of academic issues. It consists of poor academic performance and general learning deficiencies. International students who study abroad have learning difficulties adjusting to the Indonesia’s academic and social systems Learning difficulties of international students encompass the range of barriers that international students face while striving to succeed in their academic pursuits within the Indonesian higher education system. This research is a comparative descriptive type research with the quantitative method. The population of this research is international students from Universitas Negeri Padang and Universitas Jambi. The number of samples is 30 international selected using Total Sampling Method.The research instrument used was Google form survey questionnaire with Likert Scale type. Data were analyzed using descriptive statistical technique and Mann-Whitney technique with the help of the SPSS 25 program. The results of the study revealed that (1) the learning difficulties of international students were in the very high category (2) language barrier aspect was in the high category whereas social barrier and dissatisfaction of lecturers were in the very high category, and (3) there was no significant difference between the learning difficulties faced by international students from Universitas Negeri Padang and Universitas Jambi. Based on the research findings, it is suggested to counseling teachers or counselors to be able to provide guidance and counseling services which are information services, individual counseling services, and group guidance services to international students, in order to help them overcome their learning difficulties.